Relationships among barodontalgia prevalence, altitude, stress, dental care frequency, and barodontalgia awareness: a survey of Turkish pilots - Celalettin Topbaş; Dursun Ali Şirin; Hilal Gezeravcı; Fatih Özçelik; Yelda Erdem Hepşenoğlu; Şeyda Erşahan (PeerJ, 2024)
Background Gas expansion in body cavities due to pressure changes at high altitudes can cause barodontalgia. This condition may compromise flight safety. Aim To investigate relationships among barodontalgia awareness, dental visit frequency, and barodontalgia prevalence in civilian and military pilots operating at high altitudes. Materials and Methods Civilian pilots from Turkish Airlines and military pilots from the Turkish Air Force, flying between November 2022 and January 2023, participated in this study. A 20-question survey was administered to 750 pilots, covering topics such as barodontalgia awareness, dental visit frequency, breaks after dental treatments, in-flight pain, and pain type and severity. The voluntary surveys were distributed by email. Results Of the 750 pilots, 526 completed the survey; 61% were aware of barodontalgia, and 81% of pilots who had experienced it reported pain at altitudes <2000 feet. The study revealed higher barodontalgia awareness among pilots who had experienced it, with the highest prevalence among jet pilots. Pilots with barodontalgia also showed a higher frequency of dental visits (p < 0.001). Additionally, this group reported more frequent interruption of flight due to dental treatment (IFDT), more problems experienced in flights after treatment (PFAT), and higher instances of bruxism or teeth clenching during flight, suggesting stress and anxiety (p < 0.05). Conclusions Barodontalgia, a type of pain linked to stress, significantly impacts pilot performance, and can threaten flight safety, even at lower altitudes. Thus, there is a need to educate pilots about stress management, barodontalgia awareness, and the importance of regular dental check-ups.